The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law